2018
DOI: 10.1111/eip.12761
|View full text |Cite
|
Sign up to set email alerts
|

Talking about trauma in therapy: Perspectives from young people with post‐traumatic stress symptoms and first episode psychosis

Abstract: Aim: Despite recommendations from national guidelines, individuals with first episode psychosis (FEP) are currently unlikely to have the effects of their traumatic experiences assessed and treated within psychosis treatment. This may be due to the mismatch between the objectives of trauma-specific treatments (directly targeting post-traumatic stress symptoms by talking about the trauma) and trauma-informed care (limiting practices that may retraumatise clients). We aimed to gain an understanding of what it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 62 publications
(72 reference statements)
3
28
0
Order By: Relevance
“…Our research provided a richer description of the personal implications of not having the occasion to talk about trauma, grounded in participants' testimonies and personal experiences. In line with Tong et al's [32] qualitative research on FEP, our participants agreed that conversations about trauma can be uncomfortable, yet they welcomed the idea of a professional asking them about their experiences as long as they felt safe and not judged. This supports the evidence that rates of disclosure are not in uenced by patient characteristics [31], but rather by external factors such as the reactions of those to whom the traumas are disclosed.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our research provided a richer description of the personal implications of not having the occasion to talk about trauma, grounded in participants' testimonies and personal experiences. In line with Tong et al's [32] qualitative research on FEP, our participants agreed that conversations about trauma can be uncomfortable, yet they welcomed the idea of a professional asking them about their experiences as long as they felt safe and not judged. This supports the evidence that rates of disclosure are not in uenced by patient characteristics [31], but rather by external factors such as the reactions of those to whom the traumas are disclosed.…”
Section: Discussionsupporting
confidence: 78%
“…Despite some obstacles, promoting discussion of traumatic events in people with psychosis is possible. A qualitative study conducted with participants with rst-episode of psychosis (FEP) and PTSD found that, although people might initially experience di culty acknowledging that a trauma has occurred, it is possible to enhance their willingness to talk about trauma by giving them enough time and control over how trauma memories are shared [32]. Another qualitative study investigating the perspectives of young people with PTSD and FEP found that 86% of the participants showed improvement in both their PTSD and psychotic symptoms after talking about trauma, and reported that all participants found disclosure to be bene cial and worthwhile [33].…”
Section: Introductionmentioning
confidence: 99%
“…Among those accessing EIS, perceptions of safety and validation within the therapeutic relationship have been found to facilitate disclosure of significant trauma experiences (Jansen et al, 2018). Findings demonstrate the need for trauma‐sensitive practices which promote service user choice and control in trauma disclosure (Tong et al, 2018) and may lead to the identification of appropriate trauma‐focussed treatments (Schäfer & Fisher, 2011). TIC has been shown to enhance treatment retention (Mihelicova et al, 2018); therefore, with outcomes in EIS strongly linked with engagement (Jones et al, 2019) the adoption of more consistent TIC practices could increase opportunities for service users to avail of positive outcomes of EIS (Adamson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of a qualitative literature review investigating disclosures of child sexual abuse, where, in the content of shame, self‐blame and fear, disclosure was similarly viewed as an ongoing, iterative process facilitated within a relational context (Alaggia, Collin‐Vezina, & Lateef, 2017). Young people have also described reluctance to approach trauma memories and difficulty acknowledging that trauma has occurred in trauma‐informed psychotherapy (Tong, Simpson, Alvarez‐Jimenez, & Bendall, 2018). Continuity of care appears critical for young people, as has been reported by adult survivors of child sexual abuse (Chouliara et al, 2011), where abrupt changes to therapists can lead to non‐disclosure, particularly if relational elements of service engagement have been disjointed and unstable.…”
Section: Discussionmentioning
confidence: 99%